Bridging the Gap: Development of a Patient Public Involvement Group. (15th October 2021) - Goddard, Claire; Benghiat, Helen; Berki, Frederick; Buckle, Peter; Garratt, William; O'Hara, Margaret; Walker, Elizabeth; Watts, Colin; Wykes, Victoria
Abstract: Aims: Every year, the Queen Elizabeth Hospital Birmingham (QEHB) neuro-oncology team review over 2000 individuals with brain tumour. Patient and public involvement (PPI) has been fragmented to date. Initially we invited two patient advocates and a core group of allied health professionals to meet virtually to discuss development of a local PPI group, its aims, specific goals, and timescales to maintain momentum. In March 2021 we launched "BERTI: Brain tumour Education and Research paTient and public Involvement group, West Midlands". Our inaugural meeting will be virtual in April 2021 and will be followed by three meetings per year. Method: We developed information leaflets to promote the BERTI initiative. A membership form has been developed to record baseline information (non-clinical) e.g. contact details, which tumour type the individual is interested in, which aspect of BERTI they are interested in (Education, Research or Clinical service development). Patient advocates have reviewed all patient and public facing forms. All forms have been checked by Information Governance at QEHB to ensure General Data Protection Regulation compliant. Contact details and non-clinical data will be stored in a password protected database on a NHS computer network. Information to ensure members can unsubscribe from this group is easy to find and will be done immediately. A BERTI email account has been set up with a core group of professionals having access who are all fully trained in data protection and have GDPR certification. We will produce an annual BERTI newsletter. Results: BERTI is a group for people affected by brain tumours in any way. We include patients, friends and family, health professionals and researchers who are committed to improving the care of people with a brain tumour. It is run between the QEHB and University of Birmingham (UoB). BERTI provides a forum to meet other people affected by brain tumours and - Share experiences; - Understand the condition better; - Work with clinical staff and researchers to improve clinical care and facilitate research for people living with brain tumours. We will meet three times per year, virtually at the moment but face to face once Covid restrictions ease. We will have a formal talks explaining certain aspects of brain tumour or research initiatives. Throughout, there will be dedicated time set aside for group discussions to promote a genuine two-way dialogue between health-care/research professionals and individuals affected by brain tumour. Conclusion: The PPI group will be allowed to evolve rather than start out too prescriptive. It will capitalise on its strengths and skills of its composite members. There are no set models rather principles that will provide the foundations for a group which is supported to fulfil their specific purpose. The views of the PPI group will be presented at the quarterly Neuro-Oncology Multi-disciplinary team business meetings to provide a forum to discuss issues. We aim to foster a PPI friendly environment, deliver real engagement and involvement across the group.